Influence of Altitude on Caffeine, 5-Caffeoylquinic Acid, and Nicotinic Acid Contents of Arabica Coffee Varieties - Bealu Girma; Abera Gure; Feyisa Wedajo (Journal of Chemistry)
The influence of altitude on caffeine, 5-caffeoylquinic acid (5-CQA), and nicotinic acid contents of Arabica coffee varieties grown in Southwest Ethiopia was investigated. High-performance liquid chromatography with diode array detector (HPLC-DAD) was used for the determination of the target analytes. Coffee samples were collected from four coffee varieties, named as 74112, 7454, 7440, and 74110, which are cultivated in high, mid, and low altitudes in the study area. The findings of the study showed that the contents of caffeine and 5-CQA in both raw and roasted coffee beans decrease as the growing altitude increases and, thus, for all varieties, their highest concentrations were recorded in lowland coffee beans. Nevertheless, the contents of nicotinic acid increase as the altitude rises and, thus, the highest nicotinic acid content was recorded in highland coffee samples. Besides, after roasting, the contents of caffeine were increased, whereas the contents of 5-CQA were lowered, indicating the possibility of its degradation during the roasting process. Both green and roasted coffee beans also contained relatively higher concentrations of nicotinic acids. Other than the growing altitudes, the contents of caffeine, 5-CQA, and nicotinic acid in coffee beans also vary with coffee varieties. Therefore, coffee varieties that are cultivated at various altitudes may have different biochemical compositions such as caffeine, CGAs, and nicotinic acid that could greatly influence the flavor, aroma, and stimulating attributes of coffee cup quality as well as dietary benefits.